What's hot in literacy : exemplar models of effective practice - Ortlieb, Evan; Grote-Garcia, Stephanie; Cassidy, Jack; Cheek, Earl H. (Literacy research, practice and evaluation, 2020)
Understanding how to address current trends and issues in literacy education is more important than ever, as local, state, national and international agendas are increasingly recognizing literacy as a foundation for success in all disciplines in education. To bridge that gap in understanding, this book showcases hot topics in literacy, providing teachers with research-based practices for literacy improvement. Acknowledging that learning the languages of mathematics, science, and history is quintessential to content knowledge acquisition and dissemination, the international scholars which comprise the author line-up for this edited collection describe the evidence-based research findings from their research in K-12 schools to demonstrate how literacy success is fostered across the globe. Featuring innovative approaches to early literacy, disciplinary literacy, and digital literacy, the authors also pay attention to emerging topics like social, emotional, and cultural learning. By offering a selection of timely and cutting edge insights into the trending topics in literacy education, this book is ideal reading for teachers across early childhood, elementary, middle, and high school years.